Studies on Bio-denitrification of Wastewater Using Immobilized GAC in Draft Tube Spouted Bed Reactor - Keshava Joshi; Lokeshwari Navalgund; Vinayaka B. Shet (Journal of Environmental Health and Sustainable Development)
Introduction: The draft tube-spouted bed bioreactor with GAC particles immobilized with Pseudomonas syringae is being evaluated to study the effect of suspended biomass and biofilm thickness on the rate of denitrification. Though the biofilm thickness is not directly controlled in wastewater treatment by the diffusion limitation and consequent substrate penetration in the biofilm, biofilm thickness will probably have a significant impact on bacteriological activity. Materials and Methods: The reactor studies were accomplished to study the result of dilution rate on attached biomass, suspended biomass, and biofilm thickness with nitrate reduction under steady-state conditions. A spouted bed reactor with the growth media prepared was used to study the bio-denitrification using Pseudomonas syringae. Results: The study of the attached biomass on nitrate reduction indicated that, as the attached biomass increased from 0.35 g/g to 0.54 g/g at a 0.166/h dilution rate, the nitrate reduction percentage decreased from 98.18% to 88.2%. During the study, it was observed that the biomass and biofilm thickness increased and decreased, respectively, with a rise in influent nitrate concentration and dilution rate. The rise in dilution rate as well as influent nitrate concentration throughout the study increased the rate of suspended biomass. Conclusion: The nitrate reduction rate was high with higher rates of loading in a draft tube spouted bed bioreactor, due to well-organized recirculation of the solids inside the reactor. The formation of biofilm thickness on solids is a significant character as it increases the nitrate reduction rate to meet the effluent standards.